2018
DOI: 10.24198/pjd.vol30no2.18327
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between permanent teeth eruption and nutrition status of 6-7-years-old children

Abstract: Introduction: Tooth eruption is influenced by various factors, one of them is nutritional factors. This study was aimed to obtain information regarding the relationship between the number of permanent teeth erupted with nutritional status in 6-7-years-old children. Methods: This research was cross-sectional and correlational data analysis. The study was conducted towards as much as 57 children aged 6-7 years old. The sampling method was the purposive sampling technique conducted in Tanjungsari 2 State Elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…The nutrition of the children is directly affected by food consumption and indirectly influenced by socioeconomic status and knowledge related to the diversity of food, selection, and availability of food items. 11…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The nutrition of the children is directly affected by food consumption and indirectly influenced by socioeconomic status and knowledge related to the diversity of food, selection, and availability of food items. 11…”
Section: Discussionmentioning
confidence: 99%
“…26 Furthermore literature indicated that obese children received their energy mostly from protein and fat, such as meat and milk, and less from carbohydrates. 5 Many studies 2,11,13,24,27 indicated a direct relationship between obesity and early eruption of primary and permanent teeth. This study showed that the mean eruption time of 22 out of 28 (79%) teeth was earlier among As indicated earlier that nutrition and eating habits may change the time of eruption of permanent teeth, which has a significant effect on the dental treatment delivery in pediatric dentistry due to impact in occlusal, dental caries, and timing for orthodontic intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ketidakseimbangan gizi atau biasa disebut malnutrisi dapat mengakibatkan tumbuh kembang yang terhambat, sehingga pada rongga mulut, asupan gizi yang adekuat sangat diperlukan. 11 Pertumbuhan dan perkembangan rahang pada saat remaja sangat dipengaruhi oleh asupan gizi pada masa tumbuh kembang anak. Asupan gizi yang tidak sesuai dapat menyebabkan terjadinya malnutrisi yang dapat memengaruhi pembentukan dan pertumbuhan rahang serta tulang wajah.…”
Section: Pendahuluanunclassified